2013
DOI: 10.1016/j.juro.2012.08.185
|View full text |Cite
|
Sign up to set email alerts
|

Certificate of Need Legislation and the Dissemination of Robotic Surgery for Prostate Cancer

Abstract: State based certificate of need regulations were ineffective in constraining robotic surgery adoption. Despite decreased use in high stringency markets, similar adoption rates suggest that other factors impact the diffusion of robotic prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Our study adds to the body of literature demonstrating that health care utilization may not be curbed by CON programs (5)(6)(7)(8)(9). This study is unique in examining the use versus non-use of radiation therapy by CON status, which had not been examined previously.…”
Section: Commentmentioning
confidence: 88%
“…Our study adds to the body of literature demonstrating that health care utilization may not be curbed by CON programs (5)(6)(7)(8)(9). This study is unique in examining the use versus non-use of radiation therapy by CON status, which had not been examined previously.…”
Section: Commentmentioning
confidence: 88%
“…Previous work by our group and by others has questioned the value of certificate of need laws to curtail the unfettered addition of capacity in a variety of contexts. 12,40,41 Collectively, these data suggest that opportunity for a return on investment, as typified by advantageous socioeconomic and noncompetitive climates, trump the regulatory milieu in terms of determining where these facilities open. This study should be interpreted with 2 limitations in mind.…”
Section: Discussionmentioning
confidence: 98%
“…Some been suggested that state-based certificates of need should be implemented to control RALS utilization and limit costs as they pertain to prostate cancer. 25 However, state-based regulations were ineffective in constraining robotic surgery adoption and intensity-modulated radiation therapy, another controversial, high-cost prostate cancer treatment modality. 26 As health care reform gets underway, one may expect similar constructs to be implemented in order to control RALS and health care costs while striving to improve patient outcomes.…”
Section: Consequences Of Rapid Adoption Of Robotic Surgerymentioning
confidence: 99%